Men's experience of erectile dysfunction after treatment for colorectal cancer: qualitative interview study. (18th October 2011) - Dowswell, George; Ismail, Tariq; Greenfield, Sheila; Clifford, Sue; Hancock, Beverley; Wilson, Sue
Abstract : Objectives To examine the experiences of men after treatment for colorectal cancer, identify barriers to accessing services, and suggest improvements to providing information in primary and secondary care. Design Semistructured, qualitative interview study with purposive sampling and thematic analysis. Participants 28 patients treated for colorectal cancer. Setting West Midlands. Results Most men treated for colorectal cancer experience erectile dysfunction as a consequence. Not all, however, want the same response from health professionals. Although, erectile dysfunction is profoundly stressful for most men, affecting self image, behaviour, and relationships, some do not regard it as a health priority. Many of the men were uninformed about erectile dysfunction and were unprepared for it, and the majority neither helped themselves nor asked for help. Almost none were receiving adequate, effective, and affordable care. Evidence of ageism was strong. Conclusions Unlike patients with prostate cancer, men with colorectal cancer are not routinely offered information and treatment for erectile dysfunction. Greater coordination of care and consistent strategies are needed to tackle the unmet needs of this widely diverse patient group. Currently, clinicians are inadvertently neglecting, misleading, and offending such patients; better training could improve this situation, as might the reorganisation of services. Further research is needed to determine whether trained clinical nurse specialists in colorectal cancer units could coordinate ongoing care.